The screen inferiority depends on test format in reasoning and meta-reasoning tasks - Wang, Xun; Chen, Luyao; Liu, Xinyue; Wang, Cai; Zhang, Zhenxin; Ye, Qun (Frontiers in Psychology, 2023)
Influential work has confirmed screen inferiority in reading tasks that reading on screen is less productive than reading on paper. Recent researches suggest that poor cognitive performance in screen environments may be primarily due to cognitive defects rather than technological flaws. Although some studies have explored screen inferiority in reasoning tasks from cognitive and metacognitive perspectives, related theories have yet to be enriched. Here, we found that screen inferiority exists in reasoning performance regardless of the test format (multiple-choice VS. open-ended), which may result from shallow processing consistent with the previous findings. However, meta-reasoning monitoring showed screen inferiority only in the multiple-choice test format. Our results indicate that the screens exhibit robust inferiority in reasoning scores, while the influence of the media on meta-reasoning may vary with external triggers. Our research may shed light on how to conduct efficient reasoning in the screen age.